Quality family meal times in promoting good social adjustment among adolescents - Yong, Elaine *; Yu, Christine Lee Mei (Sunway University College, 2008)
The proportion of families eating together has decreased over the years and few findings exist to examine the importance of family meal time quality and its impact on family members? well being. This study aimed to examine the relationship between the quality of family meal times and adolescents? social adjustment. In this study, the family meal is defined as the meal eaten by a person who lives in a multi-person household which takes place at home. Participants consisted of 120 students (males = 60; females = 60) aged 16-18 years old from Tawau, Sabah. The Family Meal Time Questionnaire, Family Functioning Scale (FFS) and Rosenberg Self-Esteem Scale (RSE) were administered to investigate self-esteem and perception of family functioning as mediating variables for adolescent social adjustment. Results demonstrated quality family meals were significantly related to higher levels of self-esteem (r = .318, p<.01) and better perceptions of one?s family function (r = .650, p<.01). In conclusion, family meal time may promote better adolescent?s mental health.